Analysis of genetic diversity of Ven dog breed based on microsatellite markers - Nguyen Thi, Dieu Thuy; Le, Cong Trieu; Huynh Thi , Phuong Loan; Bui Thi, Tra Mi; Nguyen, Huy Tuong; Do Vo, Anh Khoa (Academia Journal of Biology, 2024)
Microsatellite (MS) is a genetic marker widely used in the studies of pedigree, individual identification, gene mapping, and genetic diversity within and between populations. The genetic diversity of the indigenous Ven dog breed, along with two imported dog breeds, the Berger and Poodle dogs raised in Vietnam, was analyzed based on seven microsatellite markers. A total of 32 alleles, an average number of alleles/loci of 4.6 were observed across 80 samples of the three dog breeds. The overall polymorphic information content (PIC) was 0.67 representing the quality of selected MS markers. Genetic diversity indices (Ho, He, Fit, Fst) showed the phenomenon of inbreeding between individuals in the Ven dog population. The genetic similarity level and phylogenetic tree also reasonably reflect the genetic relationship between the three analyzed dog breeds, in which the Ven dog showed a higher genetic distance compared to two imported dog breeds.